2021
DOI: 10.3389/fmolb.2021.699929
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Extracellular Vesicles in COVID-19 Treatment: Opportunity and Challenge

Abstract: SARS-CoV-2 infection has become an urgent public health concern worldwide, severely affecting our society and economy due to the long incubation time and high prevalence. People spare no effort on the rapid development of vaccine and treatment all over the world. Amongst the numerous ways of tackling this pandemic, some approaches using extracellular vesicles (EVs) are emerging. In this review, we summarize current prevalence and pathogenesis of COVID-19, involving the combination of SARS-CoV-2 and virus recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 206 publications
(209 reference statements)
0
25
0
Order By: Relevance
“…Studies have demonstrated that the therapeutic mechanisms of MSCs are largely mediated through the release of paracrine factors like MSC-EVs ( 63 ). MSC-EVs may also be amenable to a broader range of delivery methods, such as aerosol inhalation, which may be particularly relevant in the context of COVID-19 ( 64 ). Although we were unable to perform subgroup analysis to compare the efficacy of MSC-EVs to their parent MSCs in this first edition of our living systematic review, we anticipate that an analysis of this nature will be possible in future updates.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that the therapeutic mechanisms of MSCs are largely mediated through the release of paracrine factors like MSC-EVs ( 63 ). MSC-EVs may also be amenable to a broader range of delivery methods, such as aerosol inhalation, which may be particularly relevant in the context of COVID-19 ( 64 ). Although we were unable to perform subgroup analysis to compare the efficacy of MSC-EVs to their parent MSCs in this first edition of our living systematic review, we anticipate that an analysis of this nature will be possible in future updates.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 caused by the SARS-CoV-2 virus (severe acute respiratory syndrome coronavirus type 2) mainly affects the lungs but has also severe effects on multiple other organ systems (cardiovascular, gastrointestinal, hematopoietic, renal, and immune system). The disease is associated with a dysregulated cytokine profile, pathological changes of platelet and lymphocyte numbers, as well as endothelial dysfunction and often involves microthrombosis in the lungs, and acute thrombotic events such as stroke or venous thromboembolism with severe cases presenting with sepsis and multiple organ failure finally leading to death ( Fajgenbaum and June, 2020 ; Koupenova and Freedman, 2020 ; Elbadawi et al, 2021 ; Yan et al, 2021 ). EVs of different cellular origin circulate in plasma of COVID-19 patients ( Zaid et al, 2020 ; Campello et al, 2021 ) and can trigger distinct metabolic and transcriptional responses in recipient cells ( Lam et al, 2021 ).…”
Section: Roles Of Evs In Inflammation Cancer and Thrombosismentioning
confidence: 99%
“…The COVID-19 pandemic has pushed doors and opened new avenues in certain research areas [ 90 ]. Several trials were registered during the pandemic to explore the untapped potential of EVs in lung pathology associated with SARS-CoV-2 infection [ 91 ]. Clinical trials NCT04491240, NCT04276987, NCT04602442, and NCT04313647 are focused on investigating the safety and efficacy of MSC-derived EVs as an aerosol inhalation to harness the cytokine storm in severe hospitalized patients [ 92 ].…”
Section: Clinical Trials Evaluating Peripherally Targeted Extracellul...mentioning
confidence: 99%